Malay youth entrepreneurship in Malaysia: an empirical update - Chan, Kim Ling @ Geraldine; Sivapalan Selvadurai,; Bahiyah Abdul Hamid, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2009)
Youth entrepreneurship figures prominently in the development agendas of many developing countries including Malaysia. This paper offers a glimpse into what empirically constitutes contemporary Malaysian youth entrepreneurship through an analysis of the findings of a field research involving 531 youth entrepreneurs located in the country’s Klang Valley. The aim is to arrive at a general profiling of the youths in terms of personality traits, socio-economic background, nature of business activities and level of enterprise development. The study found that Malaysian youth entrepreneurs were mostly Malay males, aged between 25 and 40, had an upper secondary and university education, married, and possessed the normal business attributes of willingness to take risk, to work hard, to continually learn, and to be undaunted by challenges. They had participated in at least a business course and were running enterprises they built rather than inherited. Their enterprises, mainly of the sole proprietorship type and set more for selling goods than services , had been running for the past one to ten years. They started with less than RM50,000 (USD 15,000) initial capital, employed up to seven male and female employees, and were at a moderate development stage at the time of the study. The paper concludes that the insights this study had furnished qualify, if not contradict, the stereotype long held about the relative inability of Malays to participate in competitive modern business, and may thus help agencies concerned with the economic development of the nation’s youths to finetune their intervention strategies.